2021
DOI: 10.3389/fimmu.2021.732826
|View full text |Cite
|
Sign up to set email alerts
|

CMV Infection and CMV-Specific Immune Reconstitution Following Haploidentical Stem Cell Transplantation: An Update

Abstract: Haploidentical stem cell transplantation (haploSCT) has advanced to a common procedure for treating patients with hematological malignancies and immunodeficiency diseases. However, cure is seriously hampered by cytomegalovirus (CMV) infections and delayed immune reconstitution for the majority of haploidentical transplant recipients compared to HLA-matched stem cell transplantation. Three major approaches, including in vivo T-cell depletion (TCD) using antithymocyte globulin for haploSCT (in vivo TCD-haploSCT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 117 publications
0
11
0
Order By: Relevance
“…Identical) as an independent risk factor for CMV and EBV co-reactivation. Compared with HLA identical sibling transplantation, patients undergoing HLA-haploidentical stem cell transplantation(haploSCT) usually receive more intensive immunosuppressors to guarantee engraftment and later prevent graft-versus-host disease (GVHD) (Luo et al, 2021). Previous studies have shown that risk factors for CMV reactivation after HSCT include a donor or recipient seropositive for CMV, mismatched or unrelated donors, pre-allo-HSCT viremia, and use of alemtuzumab (Sousa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Identical) as an independent risk factor for CMV and EBV co-reactivation. Compared with HLA identical sibling transplantation, patients undergoing HLA-haploidentical stem cell transplantation(haploSCT) usually receive more intensive immunosuppressors to guarantee engraftment and later prevent graft-versus-host disease (GVHD) (Luo et al, 2021). Previous studies have shown that risk factors for CMV reactivation after HSCT include a donor or recipient seropositive for CMV, mismatched or unrelated donors, pre-allo-HSCT viremia, and use of alemtuzumab (Sousa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Cytomegalovirus (CMV) infection remains another challenging obstacle in transplant recipients ( 17 ). Prophylactic and preemptive antiviral treatment strategies has greatly reduced the morbidity and mortality of CMV infection post allo-HSCT, but the reconstitution of CMV-specific CTL (CMV-CTL) following transplantation is essential to confer long-term protection against CMV infection ( 18 , 19 ). The interplay between CMV infection and primary disease relapse in patients with hematological malignancies after allo-HSCT has been an area of interest and controversy for several years.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of donor serostatus on patients with IEI and cytomegalovirus infection is not yet clearly elucidated. In addition, we have to take into account that the conditioning regimen could also modify the immune reconstitution and the transferred T cell immunity of the donor, the rate of CMV reactivations, and, therefore, the long-term survival [ 33 ]. Other approaches such as the use of ATG, ex vivo T-cell depletion using CD34 + positive selection, or post-transplant cyclophosphamide could affect the control of viral replication, leading to a higher incidence of CMV infection [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%